Fatores da satisfação e fidelidade de clientes: um estudo no setor de telefonia móvel celular - Pereira, Marcio Antonio Dias (2006)
This thesis deals with the factors affecting customer satisfaction and loyalty in the mobile phone telecom sector. It is adapted a model proposed by Johnson et al. (2001) of quality and loyalty antecedent factors. It is conducted a survey with a sample of 385 customers of mobile phone telecom sector in Teresina city, a capital of a Northeastern State of Brazil, and descriptives and multiple regression statistical analysis. The main findings related to satisfaction are that quality and service price are the significant factors affecting it. Regarding loyalty, satisfaction, image, affective commitment, and calculate commitment are the significant factors to explain it. The overall model used fairly explain the satisfaction and loyalty outcomes